2007
DOI: 10.1080/09540120601017464
|View full text |Cite
|
Sign up to set email alerts
|

Time perspective and quality of life among HIV-infected patients in the context of HAART

Abstract: We explored associations between time perspective (TP) and quality of life (QOL) among HIV-infected patients. With the French validated version of the Zimbardo Time Perspective Inventory, we evaluated the TP of patients. A self-administered questionnaire gathered information about QOL (WHOQOL-HIV), TP, relationship with medical staff and self-reported side effects of HAART. Six scores of QOL - physical, psychological, social relationship, environment, patient independence and spirituality were used as dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 22 publications
0
20
0
7
Order By: Relevance
“…For example, most studies found that physical QoL of symptomatic and AIDS patients is significantly poorer than that of patients who are at a lesser advanced stage of the disease [12,15,17,21,25,26,[33][34][35][36]. Associations between physical dimensions, but not psychological dimensions have also been shown in some studies [21,25,37]. Among the biological markers, higher CD4?…”
Section: Sociodemographic and Clinical Variablesmentioning
confidence: 89%
See 1 more Smart Citation
“…For example, most studies found that physical QoL of symptomatic and AIDS patients is significantly poorer than that of patients who are at a lesser advanced stage of the disease [12,15,17,21,25,26,[33][34][35][36]. Associations between physical dimensions, but not psychological dimensions have also been shown in some studies [21,25,37]. Among the biological markers, higher CD4?…”
Section: Sociodemographic and Clinical Variablesmentioning
confidence: 89%
“…Among the biological markers, higher CD4? T cell count have been found to be associated with higher QoL scores [17,19,38], particularly in the domains related to physical and independence QoL [25,37]. Some studies, however, have not reported significant associations between CD4?…”
Section: Sociodemographic and Clinical Variablesmentioning
confidence: 94%
“…Higher levels of depression and anxiety were also predicted by higher negative perceptions of the past in individuals diagnosed with chronic diseases such as diabetes (Livneh and Martz 2007). In HIV-infected patients, impaired physical, environmental, and level-of-independence quality of life have been associated with a weak orientation towards taking pleasure in the present (Preau et al 2007). Higher scores on positive past, hedonistic present, and future have been revealed in adolescents who reported a secure attachment to parents, signifying better psychological well-being (Laghi et al 2009b).…”
Section: Introductionmentioning
confidence: 96%
“…Several studies provide support for the importance of considering this psychological construct in chronic illness experience, as diabetes (Martz & Livneh, 2007), HIV (Préau, Apostolidis, François, Raffi, & Spire, 2007), and inflammatory bowel disease (Laguette et al, 2013). In addition, it can be hypothesized that TP, as a situationally determined psychological construct, is related to socioeconomic deprivation and precariousness (Boniwell & Zimbardo, 2004;Zimbardo & Boyd, 1999).…”
mentioning
confidence: 98%